Exploring use of a commercial passive sampler in a closed static chamber to measure ammonia volatilization - Sabrina, Jaeman; Nurulhuda, Khairudin; Mohd Amin, Adibah; Sulaiman, Muhammad Firdaus; Che Man, Hasfalina (Elsevier, 2022)
Studies have indicated that up to 47% of total N fertilizer applied in flooded rice fields may be lost to the atmosphere through NH3 volatilization. The volatilized NH3 represents monetary loss and contributes to increase in formation of PM2.5 in the atmosphere, eutrophication in surface water, and degrades water and soil quality. The NH3 is also a precursor to N2O formation. Thus, it is important to monitor NH3 volatilization from fertilized and flooded rice fields. Commercially available samplers offer ease of transportation and installation, and thus, may be considered as NH3 absorbents for the static chamber method. Hence, the objective of this study is to investigate the use of a commercially available NH3 sampler/absorbent (i.e., Ogawa® passive sampler) for implementation in a static chamber. In this study, forty closed static chambers were used to study two factors (i.e., trapping methods, exposure duration) arranged in a Randomized Complete Block Design. The three trapping methods are standard boric acid solution, Ogawa® passive sampler with acid-coated pads and exposed coated pads without casing. The exposure durations are 1 and 4 h. Results suggest that different levels of absorbed NH3 was obtained for each of the trapping methods. Highest level of NH3 was trapped by the standard boric acid solution, followed by the exposed acid-coated pads without casing, and finally acid-coated pads with protective casing, given the same exposure duration. The differences in absorbed NH3 under same conditions does not warrant direct comparison across the different trapping methods. Any three trapping methods can be used for conducting studies to compare multi-treatments using the static chamber method, provided the same trapping method is applied for all chambers.